Juhūdu KH. Ahmad Haris Shodaqo fī Nashri Al-Ahādis Al-Sūfiyah fī Indonesia - Mustaghfirin, M. Khairul; Abdul Aziz Monadhel (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This article aims to explain the effort of KH. Ahmad Haris Sodaqo in the publish of sufistic orientation and approach in interaction with the sunna of Prophet Muhammad, the Messenger of Allah, and interpreting the hadith literature and traditions. It is distributed, shared and promoted by contemporary Nusantara Scholar, namely KH. Ahmad Haris Sodaqo from Semarang, Central Java, in his translate, the book elucidates hadiths of Tasawuf which offer advice for those seeking to understand of the heart and how to treat the pattern of explanation, steeped in Sufism, is Hadith students studying whether Sufism contradicts the Hadith The author employs an analytical methodology, combining literature review with classical and contemporary hadith literacy, to the sources from which the traditions are rawn. The researcher utilized the method of scholars Imam al-Iroqi, in analyzing the traditions from of the book of Ihya Ulumiddin. In evaluating the traditions, the researcher consider the opinions of jarh wa ta'adil scholars such as Tirmidzi, Hakim, Daruquthni, al-Iroqi, al-Haisami, ad-Dzahabi, al-Midzi, Ibn Hajar al-Asqolani, and modern scholars such as ar-Nauth.  The research results both in terms of quantity and quality of Hadiths, a rich Sufistic content in the style of presentation and pattern interpretation. This orientation and interpretation promote moderation among Muslims, guiding them to adopt a way in life.